Pengaruh Bimbingan Kelompok Melalui Permainan Outbound untuk Meningkatkan Penyesuaian Diri Siswa Kelas VI - Zahro, Indah Fajratuz; Rahayu, Wiwik (Program Studi Bimbingan dan Konseling Islam, 2023)
This research aims to determine the effect of group guidance through outbound games to improve the self-adjustment of class VI MII Pejambon students. Using quantitative experimental methods with a one group pretest-posttest design type of research. The population is 21 class VI MII Pejambon students. The sampling technique used was stratified sampling and a sample of 11 students with low self-adjustment was obtained. Researchers used data collectors in the form of a Guttman scale with alternative choices, namely yes and no. The scale was administered to class VI students at MII Karangdowo, SDN Karangdinoyo and SDN Pejambon. From the research results, it is known that the posttest results of the experimental class have an increase in value from the pretest results before treatment was carried out. The sig value is 0.000 < 0.05, which is the influence of group guidance through outbound games to improve the self-adjustment of class VI MII Pejambon students